The Impact of American Legislation on the Development of the Cyber Insurance Market in the US - Strupczewski, Grzegorz (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2017)
The aim of the paper is to analyse the role of regulation in stimulating demand for cyber insurance on the example of the US insurance market. This paper adds in-depth comparative analysis of American legislation to the existing scientific achievements, in particular state legislation, in the area of legal responsibility for data breach. This makes it possible to verify the oft-repeated argument that the legislation in the area of personal data security and electronic processing of personal data can stimulate the development of cyber insurance. One of the functions of such insurance is to protect the entity processing personal data from the financial consequences of administrative penalties and third party claims arising from breach of confidentiality. The study shows that state and federal regulations have a clear influence, requiring mandatory notification of data breach, on the development of the cyber insurance market in the US. Therefore, it can be expected that the implementation of similar regulations in the European Union will trigger a positive effect on the European market for cyber-insurance, which is currently in its initial development stage.